Characterization of Cassava Mosaic Disease for Identification and Analysis of Cassava Genotype TME3 Bacteria Artificial Chromosome Libraries - Kuria , Paul (Innovations in Microbiology and Biotechnology Vol. 8, 2022)
In the present study, attempts were made to assemble sequences and identify genes residing in the CMD2 locus. In sub-Saharan Africa, cassava is a significant crop commercially, however the infection with cassava mosaic disease (CMD) limits the crop's productivity potential. Traditional genetics and biotechnology are being used to combat the illness and ensure farmer harvests. The CMD2 resistance locus was mapped in West African genotypes and demonstrated to confer qualitative resistance to all species of CMGs. It is bordered by three simple sequence repeats (SSR) markers and one sequence characteristic amplified region (SCAR) marker. However, gene(s) associated with the CMD2 locus and their mode of actions remains unknown. In an effort to discover gene(s) located in CMD2 locus region, TME3 BAC collections were screened for the presence of CMD2 flanking markers. CMD susceptible and resistant cassava genotypes were found to contain 100% of the markers flanking CMD2 locus. SNPs and nucleotide deletions were identified within the marker sequences but there was no evidence of trait and marker association. All the SSR markers flanking CMD2, and the more recently characterized CMD3 loci were to be located on chromosome 12. Through BAC pools library hybridization with marker probes, 130 BACs were identified, but only 23 BACs contained at least CMD2 specific two markers. Whole BAC sequencing identified five clones that mapped to the marker regions. BAC29 assembled into a 100 kb contig and encoded tandem repeats of three full length R genes (3.5 kb) and two partial repeats. These R genes were conserved and highly expressed in CMD susceptible and CMD resistant cassava genotypes. Promoter sequences derived from R genes showed similar transient expression of GUS as 35S promoter. On cassava genome V6.1 BAC29 sequences were mapped to chromosome 16, eliminating their potential role in CMD resistant. Efforts should therefore focus on developing polymorphic molecular markers closely linked with the CMD2 locus that can easily be utilized to screen for CMD resistance. In addition, there is need for whole genome sequencing of CMD2 type cassava to identify sequences coding for genes harbored in CMD2 region.